Transplant-associated thrombotic microangiopathy is an endothelial complication associated with refractoriness of acute GvHD - Zeisbrich, Markus; Becker, Nikolaus; Benner, Axel; Radujković, Aleksandar; Schmitt, K.; Beimler, Jörg; Ho, Anthony Dick; Zeier, Martin; Dreger, Peter; Luft, Thomas (Bone marrow transplantation, 2017)
There is increasing evidence that endothelial dysfunction is involved in refractoriness of acute GvHD (aGvHD). Here we investigated the hypothesis that another endothelial complication, transplant-associated thrombotic microangiopathy (TMA), contributes to the pathogenesis of aGvHD refractoriness. TMA was retrospectively assessed in 771 patients after allogeneic stem cell transplantation (alloSCT). Incidences of TMA and refractory aGvHD were correlated with biomarkers of endothelial damage obtained before alloSCT for patients receiving or not receiving statin-based endothelial prophylaxis (SEP). Diagnostic criteria for TMA and refractory aGvHD were met by 41 (5.3%) and 76 (10%) patients, respectively. TMA was overrepresented in patients with refractory aGvHD (45.0 vs 2.3% in all other patients, P<0.001). TMA independently increased mortality. Elevated pretransplant suppressor of tumorigenicity-2 and nitrates along with high-risk variants of the thrombomodulin gene were associated with increased risk of TMA. In contrast, SEP abolished the unfavorable outcome predicted by pretransplant biomarkers on TMA risk. Patients on SEP had a significantly lower risk of TMA (P=0.001) and refractory aGvHD (P=0.055) in a multivariate multistate model. Our data provide evidence that TMA contributes to the pathogenesis of aGvHD refractoriness. Patients with an increased TMA risk can be identified pretransplant and may benefit from pharmacological endothelium protection.